Efficacy of L-arginine and Pycnogenol ® in the treatment of male erectile dysfunction: a systematic review and meta-analysis - Tian, Yuting; Zhou, Qian; Li, Wen; Liu, Meixi; Li, Qing; Chen, Qiu (Frontiers in Endocrinology, 2023)
The objective of this meta-analysis was to review clinical trials of the combination of Pycnogenol ® and L-arginine (PAL) in the treatment of erectile dysfunction in men and to observe the effect of PAL combined therapy on sexual function in ED patients, we hope to provide more choice of drugs for treating ED patients.The study was constructed according to PRISMA guidelines. We searched seven databases from inception to February 15, 2023, for a comprehensive search of clinical trials using relevant keywords. Continuous variables in this meta-analysis were calculated using the mean difference (MD) and 95% confidence interval (CI). All relevant statistical analyses were performed using Rev Man v. 5.4 software.Three studies with 184 patients were included in the present meta-analysis. There were no significant differences in the basic characteristics of the included studies. The results of the current meta-analysis showed that there were significant differences in International Index of Erectile Function (IIEF) scores (erectile domain), Intercourse satisfaction scores, Orgasmic function scores, Overall satisfaction scores, and Sexual desire scores, between the combination treatment group and the control group. There was no significant difference in improving Testosterone levels between the two groups.These results indicate that the combination of PAL may have a significant effect on improving sexual function in mild to moderate ED patients. This study will provide clinicians with more options for treating patients with ED. More randomized controlled trials are needed in the future to further demonstrate the effect of combination therapy on sexual function in patients with ED.